Model of Crisis Communication Management in the Perspective of Situational Crisis Communication Theory at the Transportation Ministry - Ari Sulistyanto; Usmar Usmar; Hermiyetti Hermiyetti (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
Rapid disaster response is necessary since it involves various stakeholders in disaster. However, rapid response is difficult to implement due to structural constraints and organizational hierarchy.  This research aims to reveal structural constraints to crisis communication management in the internal organization of the Transportation Ministry. Situational Crisis Communication Theory (SCCT) approaches offer a framework to understand management in general in responding to crisis situation.  This research uses a qualitative method with case study approaches. The results of this research show that in the pre-crisis phase the organization serves as media for sections at the Transportation Ministry to interact in monitoring potential crisis.  In the crisis and post-crisis response phases, the establishment of an Ad Hoc Crisis Communication Team (TKK) has changed the organization from being under stringent hierarchic structure to being more flexible and responsive in crisis response. This research gives contributions to more dynamic crisis communication management, recommends the formulation of Standard Operating Procedure (SOP) in crisis communication management, starting from pre-crisis, crisis to post-crisis response phases, and gives guidance to government and non-government organizations in crisis communication management.